Playing with fire: the unintended consequences of monetary financing - Dierks, Leef H. (REVISTA PROCESOS DE MERCADO, 2017)
To the extent that the ECB’s more recent monetary policies, among them cutting its main refinancing rate to a historical low of 0% in March 2016, failed to deliver the hoped for results in the wake of the financial crisis and the euro area started facing a “Japanifica-tion” (Dierks, 2015), unconventional monetary policy measures were adopted. These included unprecedented asset purchases, which caused the Eurosystem’s total assets to soar to €4.3trn (about 35% of Euro area GDP) as per mid-October 2017, the latest date for which data were available (fig. 1). Originally, these unconventional policy measures were designed to stimulate economic growth, particularly in the Medi-terranean Rim economies, and to spur inflation; “the (ECB’s) Gov-erning Council is more actively steering the size of the ECB’s balance sheet towards much higher levels in order to avoid the risks of too prolonged a period of low inflation in a situation where policy rates have reached their effective lower bound“ (ECB, 2014). In light of the most recent inflation data (fig. 2), this policy appears